The breeding of japonica rice in northern China: An 11-year study (2006–2016) - Yue CUI; Meng-meng ZHU; Zheng-jin XU; Wen-fu CHEN (Journal of Integrative Agriculture, 2020)
The world's population is facing food shortages due to climate change and the competition for arable land between food and energy crops. Many national and international projects to develop “super rice” cultivars were established in recent decades to attain a ‘third leap forward’ in rice production. In order to evaluate the breeding process in northern China, an 11-year tracking survey of japonica rice breeding, which involved a total of 520 rice accessions and 67 test plots, was completed in this study. The results showed that the yields of these accessions had increased stably, which was similar to control check varieties (CKs). The breeding strategy reduced the panicle number and increased the grain number per panicle through an increase of spikelet density (number of grains per centimeter on the panicle). This high spikelet density benefits not only the yield but also the blast resistance and amylose content. At higher latitudes, the preferred rice accessions had slim grain shape and extended growth period. In the middle latitudes among the test plots, the breeders focused on reducing the amylose content to improve the cooking quality of the rice accessions. Yield and blast resistance were the two highest priorities during the breeding selection process. The present study evaluated the breeding process in northern China during the last decade, which may lead to new insights into the future of rice breeding.